2023
DOI: 10.1145/3561048
|View full text |Cite
|
Sign up to set email alerts
|

Explainable AI (XAI): Core Ideas, Techniques, and Solutions

Abstract: As our dependence on intelligent machines continues to grow, so does the demand for more transparent and interpretable models. In addition, the ability to explain the model generally is now the gold standard for building trust and deployment of Artificial Intelligence (AI) systems in critical domains. Explainable Artificial Intelligence (XAI) aims to provide a suite of machine learning (ML) techniques that enable human users to understand, appropriately trust, and produce more explainable models. Selecting an … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
31
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 282 publications
(64 citation statements)
references
References 35 publications
1
31
0
Order By: Relevance
“…Previous studies (Dwivedi et al, 2023;Ding et al, 2022) have identified various XAI tools, and we have also listed 35 tools in Table 1. Among these tools, Shap, LIME, and Eli5 have been consistently highlighted as important tools.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies (Dwivedi et al, 2023;Ding et al, 2022) have identified various XAI tools, and we have also listed 35 tools in Table 1. Among these tools, Shap, LIME, and Eli5 have been consistently highlighted as important tools.…”
Section: Resultsmentioning
confidence: 99%
“…Additionally, XAI techniques provide versatile methods for explaining complex models; Ribeiro et al (Ribeiro et al, 2016) introduce Lime, an adaptable and expandable approach to explaining predictions in a comprehensible manner, while Lundberg et al (Lundberg and Lee, 2017a) introduce Shap, a powerful framework for interpreting predictions through feature importance values. In the case of available tools in XAI, Previous studies (Dwivedi et al, 2023;Ding et al, 2022) have identified various XAI tools, Among these tools, Shap, Lime, and Eli5 have been consistently highlighted as essential tools.…”
Section: Explainable Aimentioning
confidence: 99%
“…Then there is the when and where one applies XAI: ante hoc XAI (attribution to inputs/outputs in the pre‐modeling phase) and post hoc XAI (post‐modeling phase, e.g., LIME). Researchers also distinguish between white‐ and black‐box methods; the former concerns AI models that are simple and self‐explanatory and the latter considers opaque models and data handling prevalent in DNN (Dwivedi et al, 2023). All are used in GeoAI, as will be seen below.…”
Section: Geographic Applications Of Xai Methods: State‐of‐the‐artmentioning
confidence: 99%
“…Researchers also distinguish between white-and black-box methods; the former concerns AI models that are simple and self-explanatory and the latter considers opaque models and data handling prevalent in DNN (Dwivedi et al, 2023). All are used in GeoAI, as will be seen below.…”
Section: Linear Regressionmentioning
confidence: 99%
“…This overview is not meant to be exhaustive, but rather to highlight the various areas where XAI techniques can be applied. For a more intensive survey of current methods in XAI, we direct the reader to recent reviews [11,42] on the topic.…”
Section: Explanation Methodsmentioning
confidence: 99%